Morphological and phaneroptic traits of Creole goats reared in an extensive system in the dry forest of Tumbes, Peru - VICTOR A. TEMOCHE; DAVID J. GODOY; FRITZ C. TRILLO; NARDA ORTIZ; JUANCARLOS CRUZ (Society for Indonesian Biodiversity, 2024)
Abstract. Temoche VA, Godoy DJ, Trillo FC, Ortiz N, Cruz J. 2024. Morphological and phaneroptic traits of Creole goats reared in an extensive system in the dry forest of Tumbes, Peru. Biodiversitas 25: 4148-4161. This study aimed to characterize the phaneroptic and morphometric traits of Creole goats in Northwestern Peru. A total of 100 goats were evaluated for 19 phaneroptic and 24 morphometric variables, along with 15 zoometric indices. Descriptive statistics and Principal Component Analysis (PCA) were used to condense body index variables into uncorrelated components, potentially useful in selection programs. The feasibility of PCA was confirmed with the Kaiser-Meyer-Olkin Measure and Bartlett’s Test of Sphericity. Phaneroptic results revealed that most goats exhibit plain coats (53%) with mottled and patch patterns (13% each), with 60% showing horns (45% arched and 15% spiraling) and drooping ears (60%). Beards were present in 34% and wattles in 27%. Female teats tended to be divergent (74%), with 33.77% showing supernumerary teats. Morphometric indices indicated predominantly brevilinear, dolichocephalic, and mesoprosopic traits, with a convex linear pelvis. These traits highlight their suitability for meat production, demonstrated by body strength, depth, and width, indicating high potential for producing carcasses of various compactness levels. These findings provide valuable data on the adaptability and morphological diversity of Creole goats, supporting future conservation and breeding efforts.